A Rapid and Selective LC-MS/MS Method for Quantification of Quetiapine in Human Plasma and its Application to Pharmacokinetic Study on Indian Schizophrenia Patients - S. Ravinder; A. T. Bapuji; K. Mukkanti; M. Nagesh; H. L. V. Ravikiran (E-Journal of Chemistry)
A rapid, robust and selective high pressure liquid chromatography–positive electrospray ionization tandem mass spectrometry method has been developed and validated for the quantification of quetiapine (QUE) in human plasma with K2EDTA using oxcarbazepine (IS) as an internal standard. Analyte and internal standard were extracted from human plasma by solid-phase extraction using acetonitrile. The eluted samples were chromatographed on a C18 column by using a 10:75:15v/v mixture of ammonium formate buffer (5 mM, pH 4.50) and acetonitrile and methanol as an isocratic mobile phase at a flow rate of 0.4 mL/min and analyzed by mass spectrometry in the multiple reaction monitoring mode using the respective [M+H]+ ions, m/z 384.3/253.2 for Quetiapine and m/z 253.1/208.1 for the internal standard. The assay exhibited a linear dynamic range of 5.01 - 2501.04 ng/mL for quetiapine in human plasma. Acceptable precision and accuracy were obtained for concentrations over the standard curve range. A run time of 2.5 min for each sample made it possible to analyze 300 patient plasma samples per day. The validated method has been successfully used for the estimation of quetiapine in real time schizophrenia patient’s plasma samples for pharmacokinetic study.